The influence of leadership style and work environment on the performance of front office department employees at The Laguna Hotel, Nusa Dua - Handojo, Eleonora Angelika; Marheni, Lily; Siwantara, I Wayan (Kajian Pendidikan, Seni, Budaya, Sosial dan Lingkungan, 2025)
This study aims to analyze the influence of leadership style and work environment on employee performance in the Front Office Department of Hotel The Laguna, Nusa Dua. The research background indicates existing issues related to the new leadership style and a perceived unconducive work environment in the department, which potentially affect performance. This research employed a quantitative approach with leadership style (X1) and work environment (X2) as independent variables, and employee performance (Y) as the dependent variable. The study's population consisted of all 30 employees of the Front Office Department at Hotel The Laguna, Nusa Dua. A census sampling technique (saturated sample) was used, where the entire population served as respondents. Primary data were collected through online questionnaires disseminated via Google Forms. Data analysis was performed using multiple linear regression analysis with the aid of IBM SPSS Statistics version 27 software, preceded by data quality tests (validity and reliability) and classical assumption tests (normality, multicollinearity, heteroscedasticity, linearity). The results indicate that: (1) Leadership style does not significantly affect the performance of Front Office employees, thus Hypothesis 1 is rejected. (2) The work environment positively and significantly affects the performance of Front Office employees thus Hypothesis 2 is accepted. (3) Leadership style and work environment simultaneously (together) positively and significantly affect the performance of Front Office employees thus Hypothesis 3 is accepted.